Analisis Kesalahan Berbahasa pada Film Animasi Anak Karya Manara Studios: Ibra - Widya Nafiatus Sholikhah; Sulton Azali Amrullah; Toni Diyan Pratama; Lisma Meilia Wijayanti (CV Edujavare Publishing, 2024)
This study aims to find out what language errors are found in the object of children's animation studied, namely the children's animation series by Manara Studios: Ibra. This research method uses qualitative descriptive research with a content analysis approach to language errors. The source of data in this study is an animated video of Indonesian children contained in the Manara Studios:Ibra Youtube channel with a video duration of 10:41 minutes with the title “Makanan Jabir”. The data collection technique used is a language error analysis technique which is carried out through 4 stages, namely first determining the sample, second identifying errors, third describing errors, and finally explaining errors. The results of this study were that there were phonological errors of 18 data at the level of changes in phonemes of 12 data, removal of phonemes 2 data, addition of phonemes 2 data, and changes in diphthong sounds into Single phonemes 2 errors. Syntax errors as many as 5 data at the level of interference of the mother tongue 2 data, incomplete sentences 2 data, and errors in the use of conjunction words as much as 1 data. Morphological error as much as 4 data at the level of inaccuracy in the use of prefix 1 data, removal of Prefix as much as 3 data. And semantic errors as much as 4 data at the speaker code switching level when communicating 1 data, mixing speaker code as much as 1 data, and non-standard words in speaker sentences 2 data.